France's colonial legacies : memory, identity and narrative - Barclay, Fiona, 1973- (French and francophone studies., 2013)
France's Colonial Legacies offers a timely intervention in the debates around the French empire and its place in the life of the contemporary nation, drawing on the expertise of researchers working in the fields of politics, media, cultural studies, literature and film, to offer a wide-ranging picture of remembrance in contemporary France.